Reasserting hegemony in Central Asia: Russian policy in post-2010 Kyrgyzstan (Comillas Journal of International Relations, 2015)
While there has been considerable international focus on Russia’s assertive foreign policies in Ukraine and the southern Caucasus, Moscow’s increasing influence in the former Soviet states of Central Asia has received much less attention. A shift in policy after 2010 has been particularly successful in the development of a much stronger Russian relationship with Kyrgyzstan, a state that had previously developed a moderately pro-Western foreign policy, and which plays a key strategic role in the region. Kyrgyzstan has downgraded security and political ties with Western states, joined the Russian-led Eurasian Economic Union (EEU), and developed closer security ties in the Collective Security Treaty Organisation (CSTO). This article analyses these policy shifts and characterises the new Russian stance as “hegemonic”, indicating both Russian military, political and economic dominance in the relationship but also significant popular support in Kyrgyzstan for closer ties with Moscow. Russian policy has relied on an integrated approach to foreign policy that includes initiatives in the fields of security, economy and politics, and also forms of “soft power” and cultural influence. The case of Kyrgyzstan suggests that analysing Russian policy within the framework of hegemony is a useful way to discuss both the potential for increased influence and the significant constraints faced by Russian policy-makers in the Eurasian region.
Keywords: Russian Foreign Policy; Kyrgyzstan; Central Asia; Hegemony; Regional Security